2008
DOI: 10.1073/pnas.0804782105
|View full text |Cite
|
Sign up to set email alerts
|

The goat domestication process inferred from large-scale mitochondrial DNA analysis of wild and domestic individuals

Abstract: The emergence of farming during the Neolithic transition, including the domestication of livestock, was a critical point in the evolution of human kind. The goat (Capra hircus) was one of the first domesticated ungulates. In this study, we compared the genetic diversity of domestic goats to that of the modern representatives of their wild ancestor, the bezoar, by analyzing 473 samples collected over the whole distribution range of the latter species. This partly confirms and significantly clarifies the goat do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
241
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(263 citation statements)
references
References 24 publications
18
241
1
3
Order By: Relevance
“…Management in the wild during the Younger Dryas has been suggested for gazelles [Natufian (32)], goats [Zarzian (33)], and wild boar [Late Natufian (4,5)]. Genetic analyses of the existing populations of the ancestor of the domestic goat, the bezoar goat (Capra aegagrus), have recently indicated that management of this goat occurred over a very large area, from Eastern Anatolia to the Iranian Central Zagros, and probably predated domestication (34). The transportation of wild boar to Cyprus 12,000 years ago is one of the strongest cases for predomestic management.…”
Section: Discussionmentioning
confidence: 99%
“…Management in the wild during the Younger Dryas has been suggested for gazelles [Natufian (32)], goats [Zarzian (33)], and wild boar [Late Natufian (4,5)]. Genetic analyses of the existing populations of the ancestor of the domestic goat, the bezoar goat (Capra aegagrus), have recently indicated that management of this goat occurred over a very large area, from Eastern Anatolia to the Iranian Central Zagros, and probably predated domestication (34). The transportation of wild boar to Cyprus 12,000 years ago is one of the strongest cases for predomestic management.…”
Section: Discussionmentioning
confidence: 99%
“…In goats, the first studies based on this region highlighted the existence of several well differentiated maternal lineages, whose variability has a lower geographic structure compared to other livestock species. This evidence was first interpreted as indicating separated and independent domestication events in the Fertile Crescent and in Asia (Luikart et al, 2001;Chen et al, 2005), but more recently, by comparing the mtDNA genetic variability of domestic and wild goats, Naderi et al (2007Naderi et al ( , 2008 showed that, most probably, the domestication of Capra hircus took place in a wide geographic area centred around Southwest Asia, and was a large-scale phenomenon both from the temporal and numerical point of view. These results largely agree with archaeological evidence, which already suggested that goat domestication took place about 10,000 years ago in an area between the Zagros mountains and the Fertile Crescent, placed between the present day boundaries of Iran, Iraq and Turkey (Zeder and Hesse, 2000;Zeder, 2008).…”
Section: Analysis Of Goat Genetic Diversity With Classical Markersmentioning
confidence: 99%
“…Luikart et al (2001) interpret this lack of phylogeographic patterning as reflecting the continual transport of goats through human commerce over their entire history as domesticates. However, more recently, Naderi et al (2008) noted that such diversity of mitochondrial DNA haplogroups is also compatible with a single domestication center, with a phase of human management of wild or semi-domesticated goat populations comprising multiple mtDNA lineages, before geographic dispersion and subsequently local extinction of some haplogroups (Fernández et al 2006). Y-chromosome haplotypes from 20 living populations indicate a common origin for goat patrilines in the Levant and Maghrebian coastal regions (Pereira et al 2009).…”
Section: Goatsmentioning
confidence: 99%